Split tensile strength of self-compacting concrete containing coal bottom ash - Wan Ibrahim, Mohd. Haziman (2015)
Self-Compacting Concrete (SCC) is a flowing mixture that consolidates under its own weight and a highly workable concrete that can flow through densely reinforced and complex structural elements. The source material like a granular aggregate is often used in construction but difficult to find and the price is expensive. In developing country like Malaysia, the demand of natural sand is quite high to the rapid infrastructural growth. The aims for this paper is to study the effect of coal bottom ash on the replacement level of coal bottom ash as partial replacement of fine aggregate in SCC and to investigate the effect of coal bottom ash on the split tensile strength. The test involved designation of 0%, 10%, 20% and 30% of coal bottom ash (CBA) as a partial replacement of fine aggregate with variation of water cement ratio of 0.35, 0.40 and 0.45. The results shows that slump flow, L-box ratio and sieve segregation resistance of SCC mixtures with CBA are decreased, while T500 slump flow time increased with the increase of CBA replacement level. The highest tensile strength of SCC is 4.25 MPa achieved by control sample with the water cement ratio of 0.35 at the age 28 days. The increment of CBA replacement levels resulted in the reduction of split tensile strength and density of SCC. Meanwhile, the increment of water cement ratio was reduced the split tensile strength of SCC.